PERAN GAYA BELAJAR DALAM MENINGKATKAN KESIAPAN BELAJAR SISWA PADA KURIKULUM MERDEKA - Bondhaningtyas Anjarweni; Dini Rakhmawati; Arri Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Readiness to learn is a crucial factor in determining educational success. This concept includes motivation, cognitive, social skills, as well as individual physical and emotional conditions that support the learning process. The main indicator of readiness to learn is the ability to receive and understand the material well. The Independent Curriculum, which provides freedom for schools and teachers in preparing learning programs, emphasizes developing students' freedom of thought and creativity. Teachers play an important role in creating an interesting and effective learning atmosphere. Good learning readiness allows students to be more motivated, optimize learning outcomes, and achieve learning goals. Understanding student learning styles is also an important key for educators. Learning styles that match teaching methods can improve learning effectiveness and student academic outcomes. Conversely, a mismatch between learning styles and teaching methods can hinder student motivation and understanding. Student learning readiness can be measured through learning style assessments that help teachers plan and organize tasks according to individual needs. Learning readiness also helps students face challenges, adapt, and overcome difficulties during the learning process. Therefore, understanding and developing learning readiness is an important focus in efforts to improve the quality of education.